Finite strain of the Tertiary rocks and their relation to tectonic deformation at Al-Tib Anticline in Missan governorate, Southeastern part of Iraq - AL- Hachem, Atheer E. K.; Al-Obaidi, Mustafa R. S. (Iraqi Journal of Science, 2018)
This paper presents the finite strain results from seven oriented samples data on Tertiary sandstone of Muqdadiya Formation and (400) samples of pebbles and conglomerate of Bai –Hassan Formation at the southwestern limb of Al-Tib Anticline in the Southeastern part of Iraq. Measurement and analysis of finite strain are carried out including these rocks at fluvio- lacustrine environment. The present study followed Fry method. The computed strain was, in the form of ellipses, within three prepared perpendicular planes in a single sample and Center to Center method was used to determine the strain ratio of the these samples. The strain in the studied area is low, this is mainly due to the sampled rocks underwent brittle deformation during folding. The calculated axial ratios (Rs), (three dimensional orientations of the strain axes) of strained rocks are shown which is equivalent to the log Flinn diagram normally used for plotting strain ellipsoids and according to the stereographic projection method, the long axes of this ellipsoid are sub parallel to measured Al-Tib Anticline axis and the short axes are approximately perpendicular to the axis of Al- Tib Anticline in the study area. This orientation of these axes is related to the movement of the Arabian plate.